A Survey of Avifauna in Bachok District, Kelantan, Peninsular Malaysia. - R., Ramli; Z., Ya’cob; F., Aimi; Ezyan, N.H. (Malaysian Journal of Science (MJS), 2010)
A survey on bird diversity was conducted along coastal areas of Bachok, Kelantan. The aim of the study is to document avian species diversity in the proposed site for UM Marine Field Station. Field visits were conducted five times over a period of 12 months from June 2008 until May 2009. The direct observation technique was applied to record bird species. A total of 70 species of birds from 30 families were recorded in the study area. Of this, three species were introduced species, 45 were residents, 11 were migrants, and 11 species have both migrants and residents populations. Forty-eight of the recorded species are either totally protected or partially protected (two species as game birds and other two species as licence caged birds) under Protection of Wildlife Act 1976. In term of conservation status, two species (Grey-breasted Babbler, Malacopteron albogulare and Longtailed Parakeet, Psittacula longicauda) are classified as Nearly Threatened by the IUCN Red Data Book. Fifty-two recorded species are commonly found throughout Peninsular Malaysia but ten species are uncommon, seven are abundant, and a single species (Javan Pond-Heron, Ardeola speciosa) is rarely found. Bird distributions and species diversity recorded during each visit varied depending on sampling site. Generally, Bachok district possesses a wide variety of birds and can contribute significantly towards biodiversity conservation and management.